Efficient activation of peroxymonosulfate by hollow cobalt hydroxide for degradation of ibuprofen and theoretical study - Mingfeng Ma; Long Chen; Jingzhu Zhao; Liu, Wen; Ji, Haodong (Chinese Chemical Letters, 2019)
Hollow microsphere structure cobalt hydroxide (h-Co(OH)2) was synthesized via an optimized solvothermal-hydrothermal process and applied to activate peroxymonosulfate (PMS) for degradation of a typical pharmaceutically active compound, ibuprofen (IBP). The material characterizations confirmed the presence of the microscale hollow spheres with thin nanosheets shell in h-Co(OH)2, and the crystalline phase was assigned to α-Co(OH)2. h-Co(OH)2 could efficiently activate PMS for radicals production, and 98.6% of IBP was degraded at 10 min. The activation of PMS by h-Co(OH)2 was a pH-independent process, and pH 7 was the optimum condition for the activation-degradation system. Scavenger quenching test indicated that the sulfate radical (SO4• −) was the primary reactive oxygen species for IBP degradation, which contributed to 75.7%. Fukui index (f −) based on density functional theory (DFT) calculation predicted the active sites of IBP molecule for SO4• − attack, and then IBP degradation pathway was proposed by means of intermediates identification and theoretical calculation. The developed hollow Co(OH)2 used to efficiently activate PMS is promising and innovative alternative for organic contaminants removal from water and wastewater.
Keywords: activation; Cobalt hydroxid; DFT calculation; Peroxymonosulfate; Pharmaceuticals